Atomic layer etching of Silicon Oxide. (December 2019) - Kuzmenko, V.; Miakonkikh, A.; Rudenko, K.
Abstract: The atomic layer etching process for Silicon oxide is studied. The process consists of deposition step and activation step separated by pumping and purging steps. The deposition step is performed in C4F8 plasma and produces a polymer fluorocarbon film with 0.2-3 nm thickness. Then activation step is performed in Argon or Oxygen plasma with DC bias applied to the waferholder. Accelerated ions enhance reaction of fluorine atoms of the polymer film with underlaying Silicon oxide which leads to controllable saturated etching.